Effect of warm mix asphalt (WMA) technologies on the moisture resistance of asphalt mixtures - Sukhija M.; Saboo N.; Pani A. (My University, 2025)
Moisture damage has been identified as a major concern for asphalt pavements. This concern becomes more critical when the asphalt mixtures are prepared at lower mixing and compaction temperatures using technologies such as warm mix asphalt (WMA). In this study, the effect of different WMA technologies on the moisture resistance of asphalt mixtures was studied using a variety of experimental investigations including bond strength ratio (BSR), percentage coating, retained Marshall stability (RMS), and tensile strength ratio (TSR). Two aggregate sources (granite and dolomite), two base asphalt binders (VG30 and PMB40), and five WMA additives categorized under organic, chemical, and foaming technologies were used. Moisture damage in WMA mixtures was found to be a function of aggregate type and base asphalt binder. Rediset, a chemical WMA additive, showed higher moisture resistance in comparison to other technologies. Appreciable correlations were found between BSR and TSR (R2 ranged from 0.61 to 0.72). This study suggests a minimum BSR of 0.7 for satisfactory performance against moisture damage. © 2023 Elsevier Ltd